TRANSFORMATION OF LAND RELATIONS DURING MARTIAL LAW IN UKRAINE - Bohira М. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2022)
The article considers the impact of martial law on land relations, on the results of agricultural production, on environmental and food security of the state. During this period, land relations have become complicated and need to be transformed due to the fact that the legislation in the field of land relations in Ukraine is not adapted to work under martial law, and get the most products at any cost can lead to imbalances in agricultural land use and finally - to the loss of land and soil quality. That problem can and should be prevented by transforming land relations. Growing agricultural products on all agricultural lands, at the pre-war level, is possible only with the rapid victory of Ukraine in the war and bringing a significant part of agricultural lands to normal conditions (demining, leveling areas from funnels, etc.), that will take a long time. And, therefore, today it is important to ensure the maximum use of every piece of land where there is no active hostilities, without compromising the quality of soils and without violating the rights of private landowners and land users. The approaches to organization of the maximum use of agricultural lands in the conditions of war are offered. Land relations during martial law in Ukraine require improved land management and creation of the innovative state regulatory policy, development and adoption of new regulations. To ensure food security under martial law in Ukraine, it is necessary to raise awareness with the population about the obligation to cultivate all agricultural land, even those that temporarily have no owners or tenants, but for security reasons, it is necessary to have reliable information that lands are not mined. Both urban residents and temporarily displaced citizens in should be engaged in land cultivation. And that requires from the authorities to additionally make changes to the current land legislation, which will cease after the end of the war.